HUBUNGAN PENGETAHUAN, SIKAP, AKSES INFORMASI DENGAN PERAWATAN ORGAN GENITALIA EKSTERNA PESANTREN PARABEK - Zuraida Zuraida; Ida Laila (Menara Ilmu, 2020)
Abstract: Almost all women and teenagers have vaginal discharge. It is around 60% of teenagers and 40% of fertile age women (WUS). The study aimed to determine the correlation between knowledge, attitudes and information access for teenagers toward external genitalia organs care in Islamic Boarding School Thawalib Parabek in Agam Regency in 2019. This type of research was descriptive analytic with cross sectional research design. It was conducted on January to March 2019. The populations were all teenagers in Islamic Boarding School Thawalib Parabek. They were 363 people. Then, by suing proportionate random sampling technique, 78 people were chosen as the samples. The data were collected through questionnaire. Then, it was analyzed by univariate and bivariate analysis. The results of this research showed that 33.3% of respondents were less knowledgeable. Then, 42.3% of them had negative attitudes. After that, 23.1% of the respondents had less information. Next, 44.9% of them had poor maintenance access of the external genital organs. Moreover, there was a correlation between knowledge (p = 0.003), attitude (p = 0.001, OR = 5) and access to information (p = 0.001) toward external genital organs care.In short, it can be concluded that knowledge, attitudes and access to information are related to external genital organs care. Then, it is hoped that Islamic Boarding School of Thawalib Parabek stake holder provide reproductive health education to students, especially for teenagers so that their knowledge about external and maintenance genital organs care may be improved well. Keywords: Knowledge, Attitude, Access to Information, Treatment, External Genital Organs